ESP32-Based Smart Storage System with Fingerprint and HMI Integration for Workspaces - Juan Kristian Danielo S; Muhammad Naufal Ihsan R.A; Prebianto, Nanta Fakih (Journal of Applied Electrical Engineering, 2025)
Management of laboratory equipment in higher education institutions often faces challenges such as lack of supervision, difficulties in inventory tracking, and an unstructured system. To address these issues, this research designs a Laboratory Component Storage Management System that integrates fingerprint technology, proximity sensors, HMI, and a database. The proximity sensor shows a success rate of 75% in detecting objects up to a distance of 10 cm. The stepper motor system on the X, Y, and Z axes has an average error of less than 1%, supporting movement precision. The VB.NET-based interface has proven successful through black box testing, with an Admin borrowing time of 47–50 seconds and a User borrowing time of 55–70 seconds, as well as a return time of 42–45 seconds and 52–62 seconds, respectively. This system enhances security, efficiency, and user experience in the practical process and can be an alternative solution to the weakness of the manual inventory system in the laboratory.